Kota Tangguh Bencana Berbasis Komunitas: Strategi Partisipatif - Podungge, Moh. Reza; Laradjo, Moh Saldy S.T; Darwis, Darwis; Takwim, Supriadi (JURNAL RUANG / ISSN : 2085-6962, 2025)
Rapid urbanization, climate change, and social complexity make cities increasingly vulnerable to disasters. This study analyzes the role of community participation in building urban resilience against disasters through a qualitative approach and case study strategy. Data were collected through in-depth interviews, participatory observations, and document studies, then analyzed thematically. The findings show that community involvement occurs in three main stages: planning, implementation, and evaluation, with the highest effectiveness in the implementation stage. The key factors supporting effective participation include adaptive local leadership, strong social networks, and responsive policies. However, participation still faces obstacles such as resource limitations, lack of recognition of local knowledge, and communication gaps among stakeholders. This study emphasizes the importance of inclusive, contextual, and sustainable participatory strategies to collaboratively strengthen urban community resilience.